Awake microvascular decompression with fat-teflon sandwich technique: Clinical implications of a novel approach for cranial nerve neuralgias. (June 2019) - Ratha, Vishwaraj; Roopesh Kumar, V.R.; Subramaniam, Sudhakar; Kumar, Senthil; Sankaran, Vijay; Suresh Bapu, K.R.
Highlights: Re-appearance of pain following MVD is challenging and sub-optimal decompression is one of the primary factors for failure. Awake MVD provides a window for an immediate correction of sub-optimal decompression with internal neurolysis. Our modified 'Fat-teflon sandwich' awake MVD can reduce the recurrences due to Teflon slippage & granuloma. Neuroimaging negative cases & subset deemed unfit for GA have the maximum to gain with awake MVD. Abstract: Re-appearance of trigeminal neuralgia (TN) pain following microvascular decompression (MVD) is a challenging issue. A selective ablation with MVD provides the best response in such recurrences. The absence of intra-operative indicator for immediate correction of sub-optimal decompression is the primary factor for failure. We analysed the effectiveness and safety of awake MVD in minimizing failure, by tailoring the procedure according to intra-operative response with re-exploration or additional procedure like internal neurolysis in the same setting, especially in patients without vascular compression and those unfit for General Anesthesia (GA). The prospective study from June 2016 to June 2017 includes one glossopharyngeal neuralgia (GPN) and 6 trigeminal neuralgia (TN). Five cases responded with immediate complete pain relief but in 2 cases, incomplete pain relief resulted in alteration of intraoperative decision. In one case, a partial pain relief, mandated an additional internal neurolysis in the same setting, resulting in complete pain relief while in the other, re-exploration revealed a hidden venous conflict, not identified on MRI following which an additional IN was performed. All cases were followed up with BNI PIS for a minimum of one year without recurrence. Awake MVD is safe and reliable intraoperative neurophysiological prognostic marker of immediate pain relief and provides a window for an immediate correction of sub-optimal decompression with Internal Neurolysis when needed, in the same setting, especially in neuroimaging negative and elderly cases unfit for GA. It has the potential to reduce the rate of re-intervention and increase the overall effectiveness of MVD by specifically ameliorating the pain burden and quality of life.